Evaluation of waste from aluminum industry as filler in Polypropylene composites - Samat, Noorasikin; Sabaruddin, Fatimah Atiyah; Meor Yusoff, Meor Sulaiman; Abang Ismawi Hassim, Dayang Habibah (Minerals, Metals and Materials Society, 2017)
White aluminum (Al) dross is the waste or by-product generated from the smelting of Al. Improper disposal of this waste will affect the sustainability of the environment. This study was aimed at investigating the feasibility of Al dross as a thermoplastic filler. Various content of Al dross (10–40 wt.%) was blended with polypropylene (PP) using an extruder. An improvement in thermal and flame resistance properties was evident, which was associated with the presence of aluminum hydroxide elements in Al dross as revealed from x-ray diffraction analysis. It was shown that the higher Al dross content in PP did cause the composites to possess high stiffness and low crystallinity. An advantage in wear properties further showed that the Al dross can be used as a filler for thermoplastics.